The Changing World Order and US-China Maritime Power Contestation in the Indo Pacific - Muhammad Zubair Cheema; Lubna Sunawar (NUST Journal of Social Sciences and Humanities)
The grand chess board of world geopolitics has effectively been dominated by the U.S since past many decades, however, economic rise of China and resultant maritime power contestation with US is rapidly changing the status-quo within Indo Pacific Region. The announcement of “Pivot to Asia” followed by “Asia Rebalance” strategies by US President Obama and labelling of Asia Pacific to a more focused “Indo-Pacific” by the President Trump clearly reflects U.S. strategic shift to the region. To counter U.S. presence in Southeast Asia and address strategic maritime vulnerability of her Sea Lines of Communications (particularly in South China Sea), China has embarked upon an ambitious military modernization plan coupled with initiation of mega economic projects in Asia. This research is focused on developing an understanding regarding the evolving and rapidly changing maritime power contestation milieu between US and China, studied through the Realist lens. It is an in-depth study of Chinese maritime vulnerability and adopted strategy to overcome it. The research employs theoretical lens of Offensive Realism for studying the U.S national strategy to retain stature of hegemon and Defensive Realist lens to study the adopted Chinese strategy to ensure her steady rise and safeguarding its strategic maritime vulnerabilities.